A qualitative analysis of control-value appraisals, positive achievement emotions, and EFL performance in a Chinese senior high school context - Yu, Weihua; Wu, Hanwei; Zhao, Wanzhu (Frontiers in Psychology, 2022)
Based on the control-value theory (CVT), this study qualitatively investigated the relationship between control-value appraisals, achievement emotions (mainly enjoyment, pride, and hope) and English-as-a-foreign-language (EFL) performance, and explored other antecedents of achievement emotions in addition to control-value appraisals. Data were collected from six Chinese high school students through two semi-structured interviews and one focus group discussion. With thematic analysis, data were analyzed under the framework of the CVT using Nvivo 11.0. Results indicate that high perceived control, high perceived extrinsic and intrinsic values could interactively predict enjoyment, pride, and hope. Low perceived control, high perceived extrinsic value and low perceived intrinsic value could interactively predict fewer positive achievement emotions (only hope) and more negative achievement emotions like fear. High perceived control, high perceived extrinsic value and low perceived intrinsic value could interactively predict fewer positive achievement emotions (only pride), and more negative achievement emotions like anguish. Besides, positive achievement emotions positively predicted EFL performance, while negative achievement emotions negatively predicted EFL performance. Moreover, factors inside classroom, factors outside classroom, and personal factors were found to be the antecedents of achievement emotions in EFL learning.